2022
DOI: 10.12911/22998993/153489
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Calcium Oxide from Green Mussel Shell with Iron Oxide as a Potential Adsorbent for the Removal of Iron and Manganese Ions from Acid Mine Drainage

Abstract: Acid mine drainage (AMD) has the characteristics of high heavy metal ion content and low pH. This study aimed to synthesize the CaO/Fe 3 O 4 composite for the adsorption of iron and manganese ions from acid mine drainage. CaO was synthesized from the shells of green mussels (Perna viridis). The CaO/Fe 3 O 4 composites were characterized using XRD, BET surface area, SEM-EDS, and VSM. The functional groups of the composite before and after adsorption were analyzed using FTIR. The adsorption of Fe(II), Fe(III), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The adsorption of Congo red and Procion red MX-5b to CaO/Fe3O4 composite was studied using UV-Vis spectroscopy adapted from Purwaningrum et al [13]. Three parameters were set as variables in this study: contact time, dye concentration, and temperature.…”
Section: Dye Adsorption Testmentioning
confidence: 99%
“…The adsorption of Congo red and Procion red MX-5b to CaO/Fe3O4 composite was studied using UV-Vis spectroscopy adapted from Purwaningrum et al [13]. Three parameters were set as variables in this study: contact time, dye concentration, and temperature.…”
Section: Dye Adsorption Testmentioning
confidence: 99%
“…The production of CaO in this study adheres to the method detailed by Purwaningrum et al (2022). The process begins with the cleaning of green mussel shells to rid them of impurities.…”
Section: Cao Preparationmentioning
confidence: 99%
“…For instance, cow bones (Ayodeji, 2018), eggshells (Hossain et al, 2021), cockle shells (Mohamed et al, 2016), fish bones (Mostofa et al, 2022), and mollusk shells (Thakur et al, 2021) have all been identified as viable sources. Additionally, mussel shells -a type of shellfish widely consumed in Indonesia -are also an abundant source of CaO (Purwaningrum et al, 2022). Approximately 20% of the shellfish constitute the edible portion, while the remaining 75-90% comprises the shell.…”
Section: Introductionmentioning
confidence: 99%